Dynamic NMR effects in breast cancer dynamic-contrast-enhanced MRI - Li, Xin (National Academy of Sciences, 2008)
The passage of a vascular-injected paramagnetic contrast reagent (CR) bolus through a region-of-interest affects tissue (1)H(2)O relaxation and thus MR image intensity. For longitudinal relaxation [R(1) ≡ (T(1))(−1)], the CR must have transient molecular interactions with water. Because the CR and water molecules are never uniformly distributed in the histological-scale tissue compartments, the kinetics of equilibrium water compartmental interchange are competitive. In particular, the condition of the equilibrium trans cytolemmal water exchange NMR system sorties through different domains as the interstitial CR concentration, [CR(o)], waxes and wanes. Before CR, the system is in the fast-exchange-limit (FXL). Very soon after CR(o) arrival, it enters the fast-exchange-regime (FXR). Near maximal [CR(o)], the system could enter even the slow-exchange-regime (SXR). These conditions are defined herein, and a comprehensive description of how they affect quantitative pharmacokinetic analyses is presented. Data are analyzed from a population of 22 patients initially screened suspicious for breast cancer. After participating in our study, the subjects underwent biopsy/pathology procedures and only 7 (32%) were found to have malignancies. The transient departure from FXL to FXR (and apparently not SXR) is significant in only the malignant tumors, presumably because of angiogenic capillary leakiness. Thus, if accepted, this analysis would have prevented the 68% of the biopsies that proved benign.